DEVELOPMENT OF A GUIDANCE ACTIVITY SET BASED ON THE THREEFOLD TRAINING PRINCIPLES TO PROMOTE LEARNING DISCIPLINE AMONG SENIOR HIGH SCHOOL STUDENTS AT MANGKON KAMALAWAT SCHOOL, BANGKOK - Aunjaroen, PhraThitikon; Woramongkhalo, PhrakhrupaladMarut; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aims to: 1) develop a set of guidance activities based on the Threefold Training (Trisikkh) to promote academic discipline among students at Mangkon Kamalawas School, Bangkok; and 2) study the effect of using the guidance activity set based on the Threefold Training to promote academic discipline among students at Mangkon Kamalawas School, Bangkok. This research was a quasi-experimental study using a sample of 15 students in the 4th year of secondary school at Mangkon Kamalawas School, Bangkok, selected through purposive sampling. The research instruments included: 1) a set of guidance activities based on the Threefold Training (Trisikkh) and 2) a questionnaire. Data were analyzed using frequency, percentage, mean, standard deviation, and statistical test (t-test). The research findings were as follows: 1) all eight activity plans were able to raise students' awareness of the importance of paying attention in classroom. Through observation and participation in each activity, it was found that students became more inquisitive, asking or answering questions more attentively in every activity. They also exhibited more composure, were more confident in expressing their opinions, and clearly acknowledged their shortcomings from participating in the activities. And 2) the results of the comparative analysis of the assessment of academic discipline levels of students at Mangkon Kamalawas School indicated positive results. A study conducted at Mangkon Kamalawas School before and after the implementation of a guidance activity package based on the Threefold Training (Trisikkh) to promote student discipline found that the level of student discipline at Mangkon Kamalawas School in Bangkok was significantly higher after the use of the activity set, with a statistical significance level of .05.